TAXATION CHALLENGES IN INTERNATIONAL E-COMMERCE TRANSACTIONS - Loso Judijanto; Caroline Caroline; Eko Cahyo Mayndarto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
International e-commerce transactions present a range of complex taxation challenges, affecting tax authorities around the world. Key challenges include difficulties in determining tax jurisdiction due to the cross-border nature of digital transactions, which creates ambiguity regarding tax collection rights. In addition, the identification and tracking of e-commerce transactions is often hampered by the anonymous and global nature of digital transactions, which enables tax evasion. The issue of tax policy harmonisation between countries is also an obstacle, given the different tax systems and rates applicable in each country. To overcome these challenges, international cooperation and multilateral agreements are needed that can create fair and efficient tax standards and procedures for all parties involved.